Digital media and innovation : management and design strategies in communication - Gershon, Richard A. (New York, NY : Routledge, 2024)
"This fully updated second edition explores the importance of innovation and innovative thinking for the long-term success of today's leading media, telecommunications, and information technology companies. The book takes an in-depth look at how smart, creative companies have transformed today's digital economy by introducing unique and highly differentiated products and services. This edition provides a detailed overview of intelligent networks and analyses disruptive business models and processes from companies involved in social media, artificial intelligence, the metaverse, smart cities and robotics among other emerging areas. From Apple to Zoom, this book considers some of the key people, companies and strategies that have transformed the communication industries. Exploring the power of good ideas, this book goes inside the creative edge and looks at what makes such companies successful over time. Digital Media and Innovation is suited to advanced undergraduate and graduate courses in media management, media industries, communication technology, and business management and innovation, and provides up-to-date research for media and business professionals"--
Keywords: Mass media -- Management; Organizational effectiveness; BUSINESS & ECONOMICS / Industries / Media & Communications Industries; BUSINESS & ECONOMICS / Development / Business Development